On the Feasibility of OFDM-Based Massive MIMO Systems with Low Resolution Quantizers - Guerreiro, João (2017)
The use of massive multiple input multiple output (MIMO) techniques combined with orthogonal frequency division multiplexing (OFDM) schemes in the downlink of broadband wireless systems is considered in this paper. It is assumed that the transmitter supports up to R simultaneous links and employs T≫R antenna elements, and we study the feasibility of very low complexity transmitters with low resolution digital-to-analog converters (DACs). It is shown that the nonlinear distortion levels for detection purposes decrease with the ratio T/R, which means that we can employ very low resolution quantizers.